Evaluation of extremely asymmetric types of distributions of geofeatures values - Kurmankozhayev, Azimkhan; Syzdykova, Guldana (Geodesy and Cartography, 2015)
Statistical and geometric patterns were disclosed that are inherent to extremely asymmetric types of formation of stochastic frequencies of geofeatures values with the help of the exponential, probabilistic, structural, and Zipf distribution laws, which are most often used to describe them. A sophisticated pattern with exponential and hyperbolic nature of the probabilistic frequencies formation development was found. Based on these features, a leading concept of using major structure-forming characteristics of the distribu- tion of variable parameters as desired theoretical distribution function was used for parameterization of an extremely asymmetric distribution model.A median and modal frequency of geofeatures distribution were defined as the theoretical parameters of the desired distribution model. A structure was constructed and formulas were derived for determination of the statistical characteristics of the recommended distribution model. Approbation of the distribution model was conducted on an example of morphometric signs empirical distributions among the localities of varying complexity and qualitative indicators of a number of gold and rare metal deposits; inhesion of its approxi- mating power and flexibility of use was revealed.